2016
DOI: 10.1186/s12872-016-0319-y
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood socioeconomic characteristics and statin medication in patients with myocardial infarction: a Swedish nationwide follow-up study

Abstract: BackgroundCoronary heart disease (CHD) and myocardial infarction (MI) are associated with neighborhood-level socioeconomic status (SES). Statins are important drugs for secondary prevention of MI. However, no study has determined whether neighborhood-level SES is associated with statin medication in MI patients. We aimed to determine whether there is a difference in statin medication rate in MI patients across different levels of neighborhood SES.MethodsAll patients in Sweden, diagnosed with incident MI from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…At the individual SES level, our study found that the education level was significantly associated with ongoing IHD management, whereas the income status was not. Similarly, previous studies also reported that IHD management may vary according to an individual’s SES, and suggested that the survivors with lower income and education levels might fail to manage themselves appropriately because of (a) a lack of knowledge related to prevention and healthy habits,28 (b) limited access to care or drugs due to economic constraints29 and (c) a lack of willingness or resources to change their lifestyles 73.…”
Section: Discussionmentioning
confidence: 86%
“…At the individual SES level, our study found that the education level was significantly associated with ongoing IHD management, whereas the income status was not. Similarly, previous studies also reported that IHD management may vary according to an individual’s SES, and suggested that the survivors with lower income and education levels might fail to manage themselves appropriately because of (a) a lack of knowledge related to prevention and healthy habits,28 (b) limited access to care or drugs due to economic constraints29 and (c) a lack of willingness or resources to change their lifestyles 73.…”
Section: Discussionmentioning
confidence: 86%
“…The literature is mixed in the direction to which inequalities in access to statins exist, where some studies suggest that individuals with lower socioeconomic position are less likely to be prescribed statins (9, 10, 15, 16) and other studies finding the opposite or no differences (6, 8, 11, 13, 14). Of these previous studies, there was limited consideration for underlying cardiovascular risk in the analyses.…”
Section: Results In Contextmentioning
confidence: 99%
“…Of these previous studies, there was limited consideration for underlying cardiovascular risk in the analyses. Some studies adjusted for cardiovascular comorbidities (8, 13, 15, 16) such as cholesterol level, diabetes status or prevalent cardiovascular events. However, we only identified one other study that comprehensively adjusted for cardiovascular risk (11).…”
Section: Results In Contextmentioning
confidence: 99%
See 2 more Smart Citations